Mammea coumarins from the flowers of Mammea siamensis - Chulabhorn Mahidol (2018)
Four new mammea coumarins, mammea E/BA cyclo D (1), mammea E/BC cyclo D (2), mammea E/BD cyclo D (3), and mammea E/AC cyclo D (4), were isolated from the flowers of Mammea siamensis, along with six known coumarins. Extensive 1D and 2D NMR experiments and other spectroscopic studies, as well as chemical transformations, were employed to determine the structures of 1-4.